2012
DOI: 10.1002/ajpa.22072
|View full text |Cite
|
Sign up to set email alerts
|

Developmental variation in ecogeographic body proportions

Abstract: While ecogeographic variation in adult human body proportions has been extensively explored, relatively less attention has been paid to the effect of Bergmann's and Allen's rules on human body shape during growth. The relationship between climate and immature body form is particularly important, as immature mortality is high, mechanisms of thermoregulation differ between young and mature humans, and immature body proportions fluctuate due to basic parameters of growth. This study explores changes in immature e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
52
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 97 publications
(144 reference statements)
10
52
0
2
Order By: Relevance
“…Similar proportional differences are already detectable in our fetal/infant sample ( Fig. 1), which is consistent with other studies of subadult body proportions (28,29). European Americans tend to have a wider and a longer ilium relative to femur length ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Similar proportional differences are already detectable in our fetal/infant sample ( Fig. 1), which is consistent with other studies of subadult body proportions (28,29). European Americans tend to have a wider and a longer ilium relative to femur length ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…By contrast, relative limb dimensions are positively congruent with environmental factors such as latitude and annual temperature. This finding is in line with other studies that also found a relationship between limb morphology and various environmental factors [35,38,44,60,61]. Upper limb dimensions were found to be significantly and strongly correlated with maximum temperature, with OTUs from warmer climates having relatively longer and more slender upper limb bones.…”
Section: Discussionsupporting
confidence: 91%
“…While earlier research showed a strong relationship between intralimb indices and temperature based upon the predictions of Allen's rule [33], other analyses have demonstrated that there may have been a considerable time lag between occupation of an environment and the expression of adaptation in limb proportions [34,35]. This 'lag' may explain recent evidence that the correlation between intralimb proportions and climate appears to be weaker than expected, and the suggestion that these traits are genetically conservative [38,65]. This evidence for long-term adaptation in limb proportions among past populations, however, sits at odds with evidence [66] demonstrating both rapid changes in limb proportions of migrant populations [67] and mechanisms of developmental plasticity that could underpin the variation we see in intralimb proportions [37,68].…”
Section: Discussionmentioning
confidence: 97%
“…Most recent analyses continue to interpret variation in human limb proportions as being adaptive in response to environmental stress (Temple et al 2008) and relatively stable throughout development (Cowgill et al 2012). This sits somewhat at odds with evidence for plasticity of human body size and limb proportions (Tanner et al 1982;Bogin et al 2002), and evidence that environmental plasticity of many phenotypic characteristics can influence heritability estimates (Wells and Stock 2011).…”
Section: Variation In Human Phenotype and Among Negrito Populationsmentioning
confidence: 99%